DRES-01. ZEB1-MEDIATED INVASIVE MESENCHYMAL TRANSITION AT THE SINGLE CELL LEVEL PROMOTES ANTI-ANGIOGENIC THERAPY RESISTANCE IN GLIOBLASTOMA. (5th November 2018) - Chandra, Ankush; Jahangiri, Arman; Chen, William; Yagnik, Garima; Garcia, Joseph; Nguyen, Alan; Weiss, Jacob; Wolf, Kayla; Lin, Jung-Ming; Mueller, Soeren; Rick, Jonathan; Diaz, Aaron; et al.
Abstract: INTRODUCTION: Bevacizumab responsiveness in glioblastoma is transient. The time course and upstream regulators of resistance still remain undefined. There is also conflicting evidence as to whether the resistance is driven by upregulated VEGF-independent angiogenic pathways or adaptation to treatment-induced hypoxia involving perivascular invasion. METHODS: We analyzed paired patient specimens before and after bevacizumab-resistance and two xenograft models of bevacizumab-resistance: (1) a multigenerational model that replicates the lengthy treatment duration in patients and (2) PDXs replicating patient tumor resistance. Transcriptional changes were studied using microarray and qPCR. Morphological changes were assessed by immunostaining; invasion was assessed by bioengineered 3D models of perivascular vs. parenchymal invasion. Stem cell enrichment was confirmed by stem cell reformation assays. RESULTS: Despite upregulated VEGF-independent pro-angiogenic genes, immunostaining revealed increased hypoxia and decreased vessel density in resistant xenografts and patient specimens, suggesting tumor growth despite effective bevacizumab-induced devascularization. Microarrays revealed overexpression of the mesenchymal subtype gene signature across resistant xenograft generations and in resistant PDXs, replicating patient specimens whose elevated mesenchymal gene signature correlated with bevacizumab treatment duration. Single-cell sequencing of bevacizumab-resistant patient specimens revealed these mesenchymal changes to arise in early cell clones with fewer mutations. Xenograft and patient specimen microarray analysis implicated ZEB1, a key mediator of mesenchymal transition and glioma-stemness, as a potential regulator of this change, with ZEB1 increasing across xenograft generations (P< 0.001). Late-generation resistant-xenografts revealed lower form factor (p< 0.001), increased perivascular and parenchymal invasion in 3D bioengineered models (p< 0.001 and p< 0.05), and larger neurospheres (p= 0.002) with higher stem cell counts (p< 0.001) versus to early-generations. CRISPR targeting of ZEB1 reversed the morphology, stem cell neurosphere formation, and mesenchymal gene expression changes defining resistance to that of bevacizumab-sensitive tumors. CONCLUSION: We identified ZEB1 as a targetable regulator of the mesenchymal change and associated perivascular invasion and stem cell enrichment defining bevacizumab resistance.